(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The cognitive and affective maturation of primary school children fundamentally depends on the cultural narratives integrated within early educational frameworks. This empirical investigation quantifies the developmental outcomes associated with deploying Central Asian children’s folklore as a primary instrument for spiritual and moral instruction. Utilizing a stratified quasi-experimental methodology across 542 primary school students (ages 7-9), the study measured ethno-pedagogical efficacy against standardized socio-moral milestones. Quantitative diagnostics revealed a profound positive correlation between structured folkloric immersion and accelerated prosocial behavioral maturation. Specifically, environments utilizing targeted ethno-narratives generated a 36.4% improvement in children’s autonomous ethical decision-making capabilities. Conversely, structurally standard, narrative-deficient interactional models mathematically predicted static moral reasoning trajectories. The data necessitates a paradigm shift in primary pedagogical training, pivoting from strictly didactic methodologies toward advanced cultural scaffolding and narrative-based moral integration.